INSTITUTIONAL OWNERSHIP, GENDER DIVERSITY, AND TAX AVOIDANCE - Getzminanto, Paskalis Indra; Hadiprajitno, Paulus Theodorus Basuki (Kesatuan Press, 2026)
This research investigates how institutional ownership influences tax avoidance among Indonesian mining firms and further evaluates the moderating role of board gender diversity in this relationship. Tax avoidance is proxied by the Effective Tax Rate (ETR). The sample consists of 125 firm-year observations of mining companies listed on the Indonesia Stock Exchange during the 2022-2024 period. The hypotheses are tested using panel regression techniques, where the Random Effects specification is selected following a series of model selection procedures. Firm size, leverage, and profitability are included as control variables to isolate the governance effect from firm-specific characteristics that may influence tax avoidance. The results indicate that institutional ownership has a significant positive effect on ETR, suggesting that higher institutional ownership is associated with lower tax avoidance and stronger tax compliance. However, board gender diversity, measured using the Blau Index, does not significantly moderate the relationship between institutional ownership and tax avoidance. These findings contribute to agency theory by reinforcing the monitoring role of institutional investors in constraining managerial opportunism in tax-related decisions. Practically, the results highlight the importance of strengthening institutional ownership structures and enhancing governance transparency to promote sustainable tax compliance in capital-intensive industries.